Managing Wasted Perishable Items Using Six Sigma Framework: Case of Food & Beverage Division Horison Hotel - Canthika, Athluna; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract â€“ Horison Hotel is a commercial business whose runs in hospitality business sector. Nowadays, the hospitality industry not only play a key role in toursim and hotel culture only, but also driving up for food and beverage revenues. It makes the food and beverage division becomes important, especially for breakfast service. Food and beverage division of Horison Hotel face waste problem where the number of waste stream exceed the number of waste allowance. Thus, this research is conducted to aim breakfast preparation amount more specifically which can resulting in waste reduction by implementing six sigma framework.Â Keywords â€“ Six Sigma, Waste Management, Food and Beverage, Hotel